HUBUNGAN KEKERABATAN BAHASA BENUAQ, TONYOOI, DAN BAHAU: KAJIAN LINGUISTIK HISTORIS KOMPARATIF - Nurul Masfufah (Kantor Bahasa Kalimantan Timur, 2019)
It is a comparative historical linguistic study that discusses about the kinship of Benuaq, Tonyooi, and Bahau languages. Those are used and exist in East Kalimantan. This research is quantitative by using lexicostatistics of Swadesh-200 lists and also qualitative by describing the kinship of those languages. The lexicostatistical calculations indicate that those three languages are related. Benuaq and Tonyooi language relation percentage is 46.15%. Benuaq and Bahau language relation percentage is 27.18%. Tonyooi and Bahau language relation percentage is 30.77%. It shows that Benuaq and Tonyooi languages are classified as one language family, Benuaq and Bahau are classified as one language group, and Tonyooi and Bahau are classified as one language group. Thus, those three languages are not classified as one language.